Drought stress tolerance and metabolomics of Medicago sativa induced by Bacillus amyloliquefaciens DGL1 - Yang, Xue; Xie, Yongli; Qiao, Youming; Chang, Feifei; Wang, Tian; Li, Junxi; Wu, Lingling; Li, Chen; Gao, Ying (Frontiers in Plant Science, 2024)
Introduction This study used Bacillus amyloliquefaciens DGL1 isolated from the arid sandy land of the Qinghai–Tibetan Plateau as the research strain and investigated the effects of DGL1 on the biomass, physiology, and metabolites of Medicago sativa under different intensities of drought stress to provide a high-quality bacterial source and a theoretical basis for the research and development of biological fertilizer suitable for arid areas. Methods The exopolysaccharides (EPS), 1-Aminocyclopropane-1-carboxylate deaminase (ACC), and phosphorus solubilizing capacity of DGL1 were determined. The effects of a DGL1 suspension on alfalfa biomass, physiological indexes, degree of peroxidation of cell membranes, and activity of antioxidant enzymes were determined after irrigating roots under drought stress. The effects on soil physicochemical properties were also evaluated, and metabolomics analysis was performed to explore the effect of DGL1 on the metabolites of alfalfa under drought stress. Results Strain DGL1 produced extracellular polysaccharide EPS and ACC deaminase and was capable of phosphorus solubilization. Treatment with DGL1 increased the biomass of alfalfa under different degrees of drought stress, significantly increased the activities of alfalfa antioxidant enzymes Super Oxide Dismutase (SOD), Peroxidase (POD), and catalase (CAT), reduced the content of MDA and H2O2, and increased the content of quick-acting phosphorus, quick-acting potassium, ammonium nitrogen, and nitrate nitrogen in the soil, thus improving soil fertility. Through metabolomics analysis, DGL1 was shown to affect amino acid metabolic pathways, such as arginine, leucine, glutamate, and tyrosine, as well as the levels of energy-providing polysaccharides and lipids, in alfalfa under 15% PEG-6000 drought stress, enhancing alfalfa’s capacity to resist drought stress. Discussion Strain DGL1 enhances the drought suitability of alfalfa and has the potential for dryland development as a biological agent.